Penaeoid Decapoda (Dendrobranchiata) from the Luoping Biota (Middle Triassic) of China: Systematics and Taphonomic Framework. (May 2014) - Schweitzer, Carrie E.; Feldmann, Rodney M.; Hu, Shixue; Huang, Jinyuan; Zhou, Changyong; Zhang, Qiyue; Wen, Wen; Xie, Tao
Abstract : Two new genera, Anisaeger and Distaeger, and three new species, Anisaeger brevirostrus, A. spiniferus, and Distaeger prodigiosus, extend the range of the Aegeridae (Dendrobranchiata, Penaeoidea) into the Middle Triassic (Anisian) of China. Seven decapod crustacean species are now known from the Luoping biota of southern China. Morphological features of shrimp that are present but rarely mentioned in the neontological literature are recognized as potentially useful in classifying fossil material, including a diaeresis on the exopod of the uropods and multiarticulate flagellae on pleopods. Unusual taphonomic features of the shrimp include fractured cuticle, preservation in lateral, dorsal, and ventral position, and twisted cephalothoraxes.